Rigged Configurations and Kashiwara Operators - Sakamoto, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
For types An⁽¹⁾ and Dn⁽¹⁾ we prove that the rigged configuration bijection intertwines the classical Kashiwara operators on tensor products of the arbitrary Kirillov-Reshetikhin crystals and the set of the rigged configurations.